“Artificial societies” and the social sciences - Lansing, J. Stephen. (2013)
Discusses the argument on the logic of social sciences. Logical views from Karl Popper in his speech in the German Sociological Association in 1961; Critical response from Theodor Adorno; Identification of the argument as a 'positivist dispute'; Popper's attack against the inductivist and naturalist concepts of science; Focus on descriptive statistics in the analysis of social forces.